Fathers and Forefathers Men and Their Children in Genealogical Perspective - Robb, Martin (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Research on fathers and fatherhood has blossomed in recent years, focusing, for the most part, on present-day fathering experiences but also beginning to uncover hidden narratives of past fatherhood. This collection aims to add something new to this expanding field by exploring the dynamic relationship between present and past fatherhoods. The popular understanding of fathers in past generations, as being detached and uninvolved in the lives of their children, can be said to play a significant part in the construction of modern fathering identities, with ideas of "new" fatherhood being played off against notions of historical fathering practices. However, research has begun to show that these popular myths often misremember the past, judging it by current standards and obscuring the diverse nature of fathering practices in the recent and distant past. A genealogical approach is able to critically examine these intergenerational constructions of fatherhood and more positively illuminate the ways in which experiences of fathering and being fathered are passed on between generations. The contributions to this collection use a genealogical approach (broadly defined) to fathering and fatherhood as a way of defamiliarizing accepted narratives and suggesting new ways of thinking about men and their relationships with their children.